Application of a new fractional radiofrequency device in the treatment of photoaging skin in Chinese patients. (18th August 2018) - Sun, Yimeng; Luo, Yao-Jia; Li, Zhengxiu; Yu, Ai jiao; Gong, Lin; Li, Yuan hong
ABSTRACT: Background and objectives : Fractional radiofrequency (FRF) has been used in the treatment of photoaged skin for a long time. This study was intended to examine the efficacy and safety of electrode pin FRF in the treatment of photoaged skin in Chinese patients. Materials and methods : Twenty healthy Chinese subjects with facial photoaged skin were enrolled in this study. Each subject received three FRF treatments at 4-week intervals. Changes of photoaging were analyzed by a global evaluation, subjective Assessment, a Mexameter, and VISIA. Results : In total, 12 of 18 patients (66.7%) and 11 of 18 patients (61.1%) had good or excellent improvement respectively according to investigator A and investigator B. Also, 13 of 18 patients (72.2%) rated their satisfaction of the overall improvement as satisfied or very satisfied. Mean melanin index and erythema index values significantly decreased between baseline and 12-week follow up ( P < 0.05). The average wrinkle percentile was increased at 12-week follow-up (79.0 ± 8.4) compared to baseline (58.8 ± 10.2). Adverse effects were limited to erythema, tiny scabs and mild pain. Conclusions : FRF is a safe and effective method for photoaging skin in Chinese patients.